Discovery and characterization of naturally occurring chalcones as potent inhibitors of bile salt hydrolases - Chun-Yu Li; Hao-Nan Wang; Guang-Hao Zhu; Li-Lin Song; Xu-Dong Hou; Peng-Chao Huo; Jie Hou; Guang-Bo Ge (Compuscript Ltd, 2022)
Bile salt hydrolases (BSHs) play crucial roles in the deconjugation of conjugated bile acids and therefore are key targets for modulating bile acid metabolism. This study aimed to identify efficacious BSH inhibitors from a natural compound library and to characterize their inhibitory mechanisms. The inhibitory potential of more than 100 natural compounds against BSH produced by Lactobacillus salivarius (lsBSH) was assayed, and several chalcones with strong or moderate lsBSH inhibitory activity were identified. Of all tested chalcones, licochalcone C and isobavachalcone showed the most potent lsBSH inhibitory activity (IC50 < 1 μM). Inhibition kinetic analyses demonstrated that both licochalcone C and isobavachalcone reversibly inhibited lsBSH-catalyzed CA-AMCA hydrolysis via a mixed manner. Docking simulations suggested that they bind lsBSH at two distinct sites mainly via hydrogen bonding and hydrophobic interactions. Additionally, licochalcone C and isobavachalcone were found to inhibit various BSHs and decrease the total BSH activity in mouse feces, thus suggesting that these agents are broad-spectrum BSH inhibitors. Collectively, our findings revealed that licochalcone C and isobavachalcone are naturally occurring inhibitors of BSH, which may serve as promising lead compounds in the development of more efficacious BSH inhibitors for modulating bile acid metabolism.